Controversies in guidelines for the control of multidrug-resistant Gram-negative bacteria in EU countries. (December 2015) - Otter, J.A.; Mutters, N.T.; Tacconelli, E.; Gikas, A.; Holmes, A.H.
Abstract: The various guidelines that are available for multidrug-resistant Gram-negative bacteria are useful, and contain broad areas of agreement. However, there are also important areas of controversy between the guidelines in terms of the details of applying contact precautions, single-room isolation and active surveillance cultures, differences in the approach to environmental cleaning and disinfection, and whether or not to perform staff and patient cohorting, healthcare worker screening or patient decolonization. The evidence-base is extremely limited and further research is urgently required to inform an evidence-based approach to multidrug-resistant Gram-negative bacteria prevention and control.